Islamic Rituals and Spirituality in Southeast Asia: An Ethnographic Study of Coastal Muslim Communities - Adinugraha, Hendri Hermawan; Al-Kasyaf, Muhammad Zheeva (Journal of Asian Wisdom and Islamic Behavior, 2025)
This study examines the practice of Islamic rituals and spirituality among Muslim communities in Southeast Asian coastal regions, where these practices have become an integral part of social and cultural life. The central issue addressed is the lack of comprehensive documentation concerning how these communities understand and practice Islamic spirituality and symbolism in the study of modernization and religious reform. Employing a qualitative approach with ethnographic methods, this study delves into various ritual practices, including Maulid, Tahlil Laut, Sedekah Bumi, Zikir, and daily Wirid. The findings reveal that coastal Muslim communities interpret these rituals as a means of strengthening social solidarity, fostering a transcendent relationship with God, and maintaining harmony with the natural environment, particularly the sea. Spirituality is practiced communally and passed down as part of a living religious habitus. Pierre Bourdieu’s theory of practice is utilized to analyze the interplay between tradition and change within the community’s social space. This research affirms that Islam in coastal areas is not monolithic but rather contextual, adaptive, and rich in symbolic meaning. The findings contribute to the study of local expressions of Islam and offer new insights into the diversity of religious practices in Southeast Asia.